Tax Surveillance and Optimization of Hotel Tax Revenues in Surabaya - Praptining Rahayu; Puput Tri Komalasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of tax surveillance on hotel tax revenue in Surabaya City. This research applies an explanatory quantitative approach using secondary panel data on hotel tax objects from 2013 to 2024. The unit of analysis is hotel tax object-year. The sample consists of 218 hotel tax objects with 1,918 observations. The dependent variable is hotel tax revenue, transformed into ln(tax revenue + 1), while the main independent variable is tax surveillance, measured as a dummy variable based on the installation year for each tax object. The data were analyzed using panel data regression with a two-way fixed effect model and clustered standard errors at the hotel tax object level. The results show that tax surveillance has a positive effect on hotel tax revenue, with a coefficient of 0.3718 and statistical significance at the 10 percent level. This coefficient indicates that after receiving tax surveillance, hotel tax revenue tends to increase by approximately 45.04 percent. Robustness checks also show a consistently positive direction of effect across several model specifications. These findings indicate that tax surveillance can serve as an instrument for local tax intensification by improving transaction monitoring, reducing information asymmetry, and strengthening data-driven tax supervision.